Safety and Efficacy of RIRS in Geriatric Patients: A Comparative Evaluation on an Age Based Manner - Gokcen, Kaan; Dundar, Gokce; Bagcioglu, Murat; Karagoz, Mehmet Ali; Gokce, Gokhan; Sarica, Kemal (Urology Journal, 2020)
Purpose: In this retrospective study, we aimed to comparatively evaluate the efficacy and safety of RIRS procedure on an age-based manner in patients younger and above 65 years. Materials and Methods: A total of 165 patients undergoing RIRS procedure for renal stones were divided into two groups on an age-based manner namely; Group 1 (n=122) patients aging < 65 years and Group 2 (n=43) patients aging above 65 years. Demographic and clinical data regarding the stone free rates, complication rates and need for secondary procedures were retrospectively evaluated. Results: Of all the patients undergoing RIRS for kidney stones, 122 were below the age of 65 (73.9%) and 43 were above the age of 65 (26.1%). Mean age value for the patients aging more than 65 years was 74.16 ± 5.03 years and in addition to higher percentage of comorbidities, serum creatinine levels as well as ASA scores were also higher in this group when compared with younger counterparts. Although there was no statistically significant difference with respect to the operative duration, stone-free rates (SFR) and hospitalization period between the two groups, both complication rates and the need for additional interventions were higher in the older patient group (p = 0.038; p = 0.032). All complications noted in the both groups were minor (Grade I) complications according to the Clavien classification system. Conclusion: RIRS procedure can be applied as an effective and safe treatment alternative for the minimal invasive management of renal stones in relatively older patients (> 65 years) with similar hospitalization as well as stone free rates noted in the younger patients. No procedure related severe complication was noted in these cases.